Strategi Guru Pendidikan IPS dalam Pembentukan Sikap Sosial Siswa Kelas VII di MTs Negeri 2 Lombok Tengah - Rohanah; Satriawan, Lalu Agus; Jamiluddin; Najamudin (Alpatih Harapan Semesta, 2023)
This study aims to determine (1) the teacher's strategy in forming the social attitudes of class VII students at MTs Negeri 2 Central Lombok. (2) The social studies teacher's efforts in overcoming obstacles to the formation of social attitudes of class VII students at MTs. Country 2 Central Lombok. The type of this research is descriptive qualitative. The techniques used in collecting data are interview techniques as the main technique and documentation and observation techniques as supporting techniques. The data sources in this research are primary data sources in the form of madrasahs, staff, and teachers at MTs. Country 2 Central Lombok. Meanwhile, secondary data sources are written documents. Data analysis was carried out by carrying out the process of data reduction, data presentation, and drawing conclusions and to check the validity of the data a triangulation process was carried out. The results of this study indicate that the teacher's strategy in forming the social attitudes of class VII students at MTs. Negeri 2 Central Lombok is a humanist strategy, Spiritual (religious) and Behavioral (environmental) Strategy. Furthermore, the efforts of IPS education teachers in overcoming obstacles to the formation of social attitudes of class VII students at MTs. Negeri 2 Central Lombok is an Individually Direct Approach to the Students and Students Concerned.